2001
DOI: 10.1097/00005768-200106001-00012
|View full text |Cite
|
Sign up to set email alerts
|

The acute versus the chronic response to exercise

Abstract: Exercise has definite acute effects on blood lipids, blood pressure, and glucose homeostasis. Exercise also has acute effects on other factors related to atherosclerosis such as immunological function, vascular reactivity, and hemostasis. Considerable additional research is required to define the threshold of exercise required to produce these putatively beneficial effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
332
3
22

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 439 publications
(380 citation statements)
references
References 64 publications
23
332
3
22
Order By: Relevance
“…In a follow‐up to this analysis, Sesso and colleagues found that, among men with multiple (≥4) CVD risk factors, those who were more active had reduced CHD risk compared with those who were less active 10. It is not surprising that physical activity is associated with lower risk of CVD in these high‐risk subgroups because many of the mechanisms for the benefits of exercise include improvements in several of these cardiovascular risk factors, including blood pressure, lipoprotein levels, and glucose tolerance 19, 20, 21…”
Section: Discussionmentioning
confidence: 99%
“…In a follow‐up to this analysis, Sesso and colleagues found that, among men with multiple (≥4) CVD risk factors, those who were more active had reduced CHD risk compared with those who were less active 10. It is not surprising that physical activity is associated with lower risk of CVD in these high‐risk subgroups because many of the mechanisms for the benefits of exercise include improvements in several of these cardiovascular risk factors, including blood pressure, lipoprotein levels, and glucose tolerance 19, 20, 21…”
Section: Discussionmentioning
confidence: 99%
“…11 A single bout of exercise was chosen for this study because it may be the initial step to investigate the effectiveness of exercise on blood pressure reduction in populations previously identified as nonresponders. 24 Training studies may not be justified without demonstrating an acute response first. Furthermore, the utilization of acute exercise responses allows for more efficacious study into possible variations in the exercise prescription for nonresponders.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, our results cannot be attributed to these differences because in blood pressure, the acute response reflects the training response. 24 On the other hand, Nami and colleagues did not include the control group in their study, which made it hard to interpret the effects of exercise training on blood pressure. Our subjects served as their own controls.…”
Section: Ambulatory Blood Pressure Monitoringmentioning
confidence: 99%
“…Many of the compensating mechanisms previously suggested like body temperature, 27,38,39 blood lipids, 40,41 glucose or insulin concentrations, 40,42 might well come into play on a shortterm basis. Long-term regulatory mechanisms like adipose tissue-related factors such as leptin 43,44 are also known now.…”
Section: Regulation Of Energy Intakementioning
confidence: 95%